Sharing Smart Cities and Future of Marketing - Sharma, Piyush; Chen, Tom (2023)
Smart cites is a theme that has been around for the last 10 - 15 years but most of its applications have been in architecture, building and infrastructure, environment and pollution control, traffic monitoring etc. As a result, it is not clear how the lives (including attitudes, expectations, and behaviours) of consumers would change in these so‐called smart cities in future and how would marketers need to adapt to the new demands imposed by the changes in the urban infrastructure and influx of emerging technologies (e.g. artificial intelligence, virtual reality etc.) in marketing. Similarly, the idea of sharing economy has emerged in recent times but its role in the proposed smart cities remains unclear. In this special session, we aim approach this topic from diverse angles, including the idea of ‘Sharing’ in the context of smart cities e.g. circular economy, redesign of urban public services e.g. education, health, sanitation, transportation etc., impact of emerging digital technologies on consumer behaviour and decision‐making, introducing digital technology readiness (DTR) and a scale to measure this individual‐level construct that represents consumers’ level of preparedness to understand, accept and adapt new technologies in everyday lives. Keywords: circular economy, consumer behaviour, digital technologies, sharing, smart cities